Treatment switching in idiopathic pulmonary fibrosis: from triple therapy to enrollment into a clinical investigational drug trial - Valenzuela, C.; Ancochea, J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
A number of pharmacological agents have been the focus of clinical trials over the past years. Although no single pharmacological agent is recommended by current guidelines, preliminary negative findings regarding the safety of a triple therapy regimen consisting of prednisone, azathioprine and N-acetylcysteine have raised the question of whether it is no longer a treatment option. More recent data have resulted in the approval of pirfenidone in Europe. Pirfenidone shows a favourable risk−benefit profile and a beneficial effect in reducing the decline in lung function in patients with IPF. This case study describes the diagnosis and initial treatment of a patient with IPF with triple therapy of prednisone, azathioprine and N-acetylcysteine (NAC) followed by inclusion into a double-blind, randomised, placebo-controlled study and subsequent open-label extension trial of pirfenidone in IPF.